A Morphological and Histological Investigation of Imperfect Lungfish Fin Regeneration - Bothe, Vivien; Schneider, Igor; Fröbisch, Nadia B. (Frontiers in Ecology and Evolution, 2021)
Regeneration, the replacement of body parts in a living animal, has excited scientists for centuries and our knowledge of vertebrate appendage regeneration has increased significantly over the past decades. While the ability of amniotes to regenerate body parts is very limited, members of other vertebrate clades have been shown to have rather high regenerative capacities. Among tetrapods (four-limbed vertebrates), only salamanders show unparalleled capacities of epimorphic tissue regeneration including replacement of organ and body parts in an apparently perfect fashion. The closest living relatives of Tetrapoda, the lungfish, show regenerative abilities that are comparable to those of salamanders and recent studies suggest that these high regenerative capacities may indeed be ancestral for bony fish (osteichthyans) including tetrapods. While great progress has been made in recent years in understanding the cellular and molecular mechanisms deployed during appendage regeneration, comparatively few studies have investigated gross morphological and histological features of regenerated fins and limbs. Likewise, rather little is known about how fin regeneration compares morphologically to salamander limb regeneration. In this study, we investigated the morphology and histology of regenerated fins in all three modern lungfish families. Data from histological serial sections, 3D reconstructions, and x-ray microtomography scans were analyzed to assess morphological features, quality and pathologies in lungfish fin regenerates. We found several anomalies resulting from imperfect regeneration in regenerated fins in all investigated lungfish species, including fusion of skeletal elements, additional or fewer elements, and distal branching. The similarity of patterns in regeneration abnormalities compared to salamander limb regeneration lends further support to the hypothesis that high regenerative capacities are plesiomorphic for sarcopterygians.